2020
DOI: 10.1007/s00418-020-01860-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of expression of genes regulating cell cycle progression in porcine ovarian granulosa cells during short-term in vitro primary culture

Abstract: The primary function of ovarian granulosa cells (GCs) is the support of oocytes during maturation and development. Molecular analyses of granulosa cell-associated processes, leading to improvement of understanding of the cell cycle events during the formation of ovarian follicles (folliculogenesis), may be key to improve the in vitro fertilization procedures. Primary in vitro culture of porcine GCs was employed to examine the changes in the transcriptomic profile of genes belonging to “cell cycle”, “cell divis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…Ożegowska et al [34] determined the gene expression profile of cultured porcine oocytes, in which estrogen stimulation caused significant downregulation of TXNIP expression during in vitro maturation. A recently described study also showed down-regulation of this gene during primary culture of porcine granulosa cells [22,35]. In agreement with these previous studies, the present study demonstrated that the TXNIP gene was downregulated in cultured porcine OECs in vitro, which may suggest that TXNIP downregulation could serve as a marker for epithelial cell growth.…”
Section: Discussionsupporting
confidence: 92%
“…Ożegowska et al [34] determined the gene expression profile of cultured porcine oocytes, in which estrogen stimulation caused significant downregulation of TXNIP expression during in vitro maturation. A recently described study also showed down-regulation of this gene during primary culture of porcine granulosa cells [22,35]. In agreement with these previous studies, the present study demonstrated that the TXNIP gene was downregulated in cultured porcine OECs in vitro, which may suggest that TXNIP downregulation could serve as a marker for epithelial cell growth.…”
Section: Discussionsupporting
confidence: 92%
“…All of the down-regulated expression genes are cell cycle related and have been described to be involved in cell division. Interestingly, a similar direction of expression of genes responsible for cell division was obtained in in vitro experiments on human [ 88 ] and porcine granulosa cells [ 89 ]. These genes affecting cell proliferation within the ovary affect granulosa cell function [ 90 , 91 ], while at the same time may cause many diseases within the ovary [ 86 , 87 ].…”
Section: Discussionsupporting
confidence: 57%
“…This gene is also important in the maturation of mouse oocytes [ 71 ]. These results provide a potential reference for the study of mammalian follicular mechanisms and provide a possible new genetic marker for the study of the pig granulosa cell cycle [ 72 ]. These data suggest that future research directions will involve the exploration of the specific functions of TNXIP in the ovary.…”
Section: Discussionmentioning
confidence: 99%